The Authenticity and Integrity of Soil and Foundation of Bayon Temple in Angkor, Cambodia. Issue 1 (September 2021) - Iwasaki, Yoshinori; Fukuda, Mitsuharu; Iizuka, Mitsumasa; McCarthy, Robert; Nakagawa, Takeshi; Ly, Vanna
Abstract: The heritage structure of Bayon in Angkor stands upon a shallow direct foundation. The high main tower stands upon thick human-made fill without special supporting elements for such a foundation as piles. The strong strength of the human-made fill that supports heavy stone structure is one of the characters defining aspects of the authenticity of the foundation of Bayon in Angkor Thom. Several methods of restoration of retaining foundation structures in Angkor in the past are reviewed in terms of authenticity.